(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article presents the health status of workers in the agro-industrial complex of the Bukhara region. The factors influencing the health status of the working population are determined. At the same time, active work and rest of workers are recommended to maintain their health.